The Implementation of Guessing Word Meaning from the Context in Teaching Reading - Tgk. Lina Rahmalia; Sofyan A. Gani; Bukhari Daud (Universitas Syiah Kuala, 2019)
This research is a quasi experimental study which intended to find out the effect of using guessing word meaning from the context on students’ reading at Ar-Raniry State Islamic University and the students’ responses toward the implementation of guessing word meaning from the context. The population was the English department students of Ar-Raniry State Islamic University (UIN Ar-Raniry) and the samples were the students at unit I and II in the academic year of 2017/2018 chosen by using random sampling technique. Moreover, the data were collected by giving pre-test, post-test and questionnaires. The finding reveals that there was a significant difference in students’ reading scores who were taught by using guessing word meaning form the context and those who were taught without using guessing word meaning form the context. In addition, the students gave positive responses toward the implementation of guessing word meaning form the context in which 91.4% students agreed that their ability in reading comprehension increased during the implementation of guessing word meaning form the context.